THE POLICY OF STATE INVESTMENT IN HYDROGEN GENERATION IN BRAZIL SINCE 2002 - Raffi, Sérgio Aldrighi; Massuquetti, Angélica; Alves, Tiago Wickstrom (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The aim of this study was to analyze the policy of state investment in hydrogen generation in Brazil since 2002. From the research methodology literature, it was found that Brazilian investments in hydrogen are directed to two segments: power generation in fuel cells to supply vehicles and stationary units and generate hydrogen with the goal of producing a fuel with a lower content of sulfur. Finally, concern for the environment has raised the demand for more fuel efficient and less polluting. In this sense, the Brazilian state investments in hydrogen are seeking to reduce the environmental impacts caused by fossil fuels.